Apoptotic Effect of Bortezomib on Pancreatic Islet Cells in STZ-induced Diabetic Rats - Ekin, Çiğdem; Karacaer, Neslihan Tekin; Tarhan Karaoğlan, Mehtap; Örün, ibrahim; Öztürk, Kamile (Makara Journal of Health Research, 2022)
Background: This study aimed to investigate the possible apoptotic role of bortezomib (BMZ) on pancreatic islets of streptozotocin (STZ)-induced diabetic rats. Methods: Sprague-Dawley rats were divided into groups that were administered BMZ alone or in combination with STZ. To evaluate the effect of BMZ on the development of diabetes, blood glucose levels were measured regularly in the animals. Islet cell viability was determined by staining the islets with fluorescein diacetate and propidium iodide. Expression of the Bcl-2 and bax genes was determined in islet cells by quantitative real-time polymerase chain reaction. Results: Administering STZ-induced hyperglycemia in the rats reduced the viability of islet cells and the bcl-2/bax ratio. In the group administered BMZ alone, the bcl-2/bax gene expression rate in islets increased significantly compared to the control group. BMZ co-administered with STZ significantly increased islet cell viability and the bcl-2/bax ratio compared to the diabetic group. Conclusions: This study demonstrates that BMZ may protect pancreatic islet cells from apoptosis by increasing islet viability and upregulating the bcl-2/bax gene expression ratio, even though it failed to protect against the destructive effect of STZ.